Best Practices Using the Discovery Learning Model on the Subject of Special Purchase Journal with HOTS Learning Oriented at Class XI Accounting Students of SMK Negeri 4 Padangsidimpuan - Aisyah Caniago (Al'Adzkiya Journal, 2022)
Teachers have an influence on the students' optimal receiving and mastering of the learning process. Therefore, the teacher must be able to choose and adjust the appropriate learning model with the material to be conveyed. The failure of teachers in teaching is not always due to a lack of mastery of the subject matter. Still, it could be because they do not know how to convey the material appropriately and adequately so that students can learn in a pleasant and not monotonous atmosphere. This study describes the author's best practice in applying higher order thinking skills (HOTS)-oriented learning. The method used in the implementation of this best practice was to apply practical accounting learning for service and trading company with the Discovery Learning model, the small group discussion, and the assignment method. The target of the implementation was students of class XI AKL Odd Semesters for the 2019/2020 Academic Year at SMK Negeri 4 Padangsidimpuan with a total of number 18 people. The material used in this learning best practice was class XI AKL material for the Odd Semester for the 2019/2020 Academic Year on the subject of the Special Purchase Journal. The results showed that the implementation of the Discovery Learning model and the method of small group discussions and assignments made students more active and fostered mutual cooperation to solve problems given by the teacher. In addition, students also become more critical thinkers during discussion activities and become more responsible for completing their assignments because the results would be compared with other groups. Moreover, students become trained to solve their own problems to complete the student worksheet provided by the teacher or related to the application of daily life. The recommendations that can be given to teachers are that they should have an innovative learning model that is more fun while for the students, it is expected that students are able to think critically in learning, not limited to memorizing theory and for the school, providing adequate facilities and infrastructure for HOTS learning to take place.